Technical research and report writing - Vinuya, Remedios V. (Makati City, Philippines : Gandwater Publications and Research Corporation, 2002)
In your English 112 you were taught, among other things, how to use the four forms of discourse: exposition, description, narration and argumentation.
Part One. Expository forms: technical writing techniques -- Part Two. Formal and informal reports -- Part Three. Letters and letters format -- Part Four. Documentation forms.
Includes bibliographical references.
Keywords: RESEARCH WRITING